Plasminogen Activator and Plasminogen Activator Inhibitor Associated with Granulomatous Inflammation: A Study with Murine Leprosy - Izaki, S; Hibino, T; Isozaki, Y; Hsu, P S; Izaki, M; Matsuo, O (Thrombosis and Haemostasis, 1984)
Plasminogen activator that is associated with the development of hypersensitivity granulomas (gPA) was partially purified from a saline soluble fraction of murine lepromas elicited in “resistant” mice, C57BL/6N. The gPA was shown to consist of two subspecies (23,000 and 48,000 in molecular weight) with essentially identical enzymologic properties. The gPA was found to be a relatively heat stable weakly alkaline serine proteinase with trypsin-like characteristics in the specificity for synthetic substrates and proteinase inhibitors. It showed a high affinity for H- D-Ile-Pro-Arg-pNA (Km = 1.4 × 10-4 M) H-D-Val-Leu-Lys- pNA (Km = 5.2 × 10-4 M), and L-pyroGlu-Gly-Arg-pNA (Km = 9.3 × 10-4 M). The gPA did not demonstrate antigenic cross reaction with urokinase-type or tissue-type plasminogen activator.Two distinct enzymatic regulators of the gPA were also demonstrated in the saline soluble fraction of the hypersensitivity granulomas. The gPA and its regulation are assumed to be correlated with macrophage activation in the hypersensitivity granulomas
Keywords: Plasminogen activator; Plasminogen activator inhibitor; Inflammation; Hypersensitivity granulomas; Murine leprosy